The Profile and Dynamics of RNA Modifications in Animals. (27th April 2017) - van Delft, Pieter; Akay, Alper; Huber, Sabrina M.; Bueschl, Christoph; Rudolph, Konrad L. M.; Di Domenico, Tomás; Schuhmacher, Rainer; Miska, Eric A.; Balasubramanian, Shankar
Abstract: More than a hundred distinct modified nucleosides have been identified in RNA, but little is known about their distribution across different organisms, their dynamic nature and their response to cellular and environmental stress. Mass‐spectrometry‐based methods have been at the forefront of identifying and quantifying modified nucleosides. However, they often require synthetic reference standards, which do not exist in the case of many modified nucleosides, and this therefore impedes their analysis. Here we use a metabolic labelling approach to achieve rapid generation of bio‐isotopologues of the complete Caenorhabditis elegans transcriptome and its modifications and use them as reference standards to characterise the RNA modification profile in this multicellular organism through an untargeted liquid‐chromatography tandem high‐resolution mass spectrometry (LC‐HRMS) approach. We furthermore show that several of these RNA modifications have a dynamic response to environmental stress and that, in particular, changes in the tRNA wobble base modification 5‐methoxycarbonylmethyl‐2‐thiouridine (mcm 5 s 2 U) lead to codon‐biased gene‐expression changes in starved animals. Abstract : Transcriptome labelling : We describe a metabolic labelling approach for rapid generation of 13 C bio‐isotopologues of the C. elegans transcriptome to study its modifications by liquid‐chromatography tandem high‐resolution mass spectrometry (LC‐HRMS). We identify the most abundant RNA modifications, study the response to environmental stress and demonstrate their dynamic behaviour.